Eŝe raz o meste âzyka hudožestvennoj literatury v sisteme funkcionalʹnyh stilej russkogo literaturno - Krylova, Olʹga A. (Stylistyka, 2004)
The current scientific theories tend to integrate in such a way that one of them contributes to the development of others. The author emphasizes the necessity of understanding what type of scientific notions elaborated by the preceding theories can be integrated into new scientific paradigms. This could be done, on the one hand, by distinguishing between the language style and the speech style, and on the other hand, between the literary tanguage with his own functional styles and the fiction language. The literary language has its own functional styles whereas the fictional language is the national language, with its own esthetic function.